6t-3t=3

Simple and best practice solution for 6t-3t=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-3t=3 equation:



6t-3t=3
We move all terms to the left:
6t-3t-(3)=0
We add all the numbers together, and all the variables
3t-3=0
We move all terms containing t to the left, all other terms to the right
3t=3
t=3/3
t=1

See similar equations:

| 73–x=15 | | 3r-2r=10 | | p-(1/4)(3)=-5/6 | | 8-4x=-7x-28 | | z^2-70=0 | | X-24=4(3-2x)= | | f^2-40=0 | | 6(-11-2x)=-42 | | k^2-88=12 | | -2=(6/7)p | | t-18=2t-50 | | 15x=15x-120 | | x+2.2=5 | | -y/5=55 | | 4–2y–4+8+4y=20 | | 6-2(5x-2)=-2 | | -.66x+9=1.22x-3 | | 4(6x+4)=244 | | 9x−4x+132=9x+60 | | -16x^2+64x+16=0 | | 2(w+8)+5w=2 | | -7=x+(-4) | | 4(y-6)+5y=12 | | 10(x-7)^2-440=0 | | 9X4-40x2+16=0 | | 6c=47/50 | | X^2+4c+24=0 | | 2.3=7.6+y | | 6x/7=2.4 | | 9c2=24c | | 200m-100m+53,075=56,375-175 | | 1=-x^2+3 |

Equations solver categories